2016
DOI: 10.12688/f1000research.8729.1
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic drug risks of mortality, infection, depression, and cancer: but lack of benefit

Abstract: This is a review of hypnotic drug risks and benefits, reassessing and updating advice presented to the Commissioner of the Food and Drug Administration (United States FDA). Almost every month, new information appears about the risks of hypnotics (sleeping pills). This review includes new information on the growing USA overdose epidemic, eight new epidemiologic studies of hypnotics’ mortality not available for previous compilations, and new emphasis on risks of short-term hypnotic prescription. The most importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 177 publications
(177 reference statements)
1
41
0
Order By: Relevance
“… 67 The ranking results for somnolence or sedation are similar to those of death and may be explained by the fact that excessive sedation or sleep is associated with infection, including pneumonia, which could ultimately lead to death. 68 , 69 There is no evidence to support or justify the use of asenapine, clozapine, iloperidone, lurasidone, paliperidone, and ziprasidone given the lack of studies conducted on their use.…”
Section: Discussionmentioning
confidence: 99%
“… 67 The ranking results for somnolence or sedation are similar to those of death and may be explained by the fact that excessive sedation or sleep is associated with infection, including pneumonia, which could ultimately lead to death. 68 , 69 There is no evidence to support or justify the use of asenapine, clozapine, iloperidone, lurasidone, paliperidone, and ziprasidone given the lack of studies conducted on their use.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and animal research, randomized controlled trials, and epidemiological studies have all reported that benzodiazepines may increase the risk of carcinogenesis and cancer mortality [ 2 ]. Attention has been paid to whether differences exist in carcinogenic potential across different benzodiazepines [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include daytime fatigue, decreased cognitive function, tolerance, dependence, impaired immune system, and increased risk of mortality. Benzodiazepine-associated excess mortality has been linked to the potential for carcinogenesis [ 2 ]. Preliminary evidence from animal studies suggested that benzodiazepines increased the risk of thyroid cancer [ 3 ] and liver cancer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is extensive literature documenting the acute and chronic adverse effects associated with hypnotic drugs, including those approved by the Food and Drug Administration (FDA) and those used off-label 7,1013. Certain hypnotics may objectively worsen sleep: benzodiazepines might worsen breathing (although the evidence is inconsistent14) and antidepressants might increase periodic limb movements15 or worsen breathing in some circumstances 16.…”
Section: Introductionmentioning
confidence: 99%